2015
DOI: 10.1590/0037-8682-0200-2014
|View full text |Cite
|
Sign up to set email alerts
|

The use of saliva as a practical and feasible alternative to urine in large-scale screening for congenital cytomegalovirus infection increasesinclusion and detection rates

Abstract: Introduction:Although urine is considered the gold-standard material for the detection of congenital cytomegalovirus (CMV) infection, it can be diffi cult to obtain in newborns. The aim of this study was to compare the effi ciency of detection of congenital CMV infection in saliva and urine samples. Methods: One thousand newborns were included in the study. Congenital cytomegalovirus deoxyribonucleic acid (DNA) was detected by polymerase chain reaction (PCR). Results: Saliva samples were obtained from all the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 8 publications
1
18
0
2
Order By: Relevance
“…The higher content of CMV DNA and much easier collection and handling suggest that buccal swabs are preferable to urine and EDTA blood samples in neonatal CMV screening programs. In particular, the use of saliva samples improved the inclusion rate in screening programs since many newborns had to be excluded due to unsuccessful sampling of urine [6]. Viral load levels in EDTA blood were more than 10 4 -fold lower than in buccal swabs (Fig 3, S3 Table), consistent with the reduced sensitivity reported for assays based on dried blood spots [22,[25][26][27][28].…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…The higher content of CMV DNA and much easier collection and handling suggest that buccal swabs are preferable to urine and EDTA blood samples in neonatal CMV screening programs. In particular, the use of saliva samples improved the inclusion rate in screening programs since many newborns had to be excluded due to unsuccessful sampling of urine [6]. Viral load levels in EDTA blood were more than 10 4 -fold lower than in buccal swabs (Fig 3, S3 Table), consistent with the reduced sensitivity reported for assays based on dried blood spots [22,[25][26][27][28].…”
Section: Discussionsupporting
confidence: 66%
“…Polymerase chain reaction (PCR) analyses of saliva samples obtained by buccal swabs have been proposed as a universal screening approach for cCMV infections by different studies (e.g. [5][6][7][8][9]). As part of the CHIMES study, 34,989 infants have been investigated for the occurrence of cCMV infection [7].…”
Section: Introductionmentioning
confidence: 99%
“…The optimal approach to diagnosing in utero congenital infection of CMV is to detect CMV DNA in urine samples of newborns within 3 weeks after birth [23,24]. However, due to the difficulty in collecting urines from newborns, saliva samples are usually used to detect CMV DNA [25][26][27][28]. In the present study, we found that the infants who were delivered virginally and/or breastfed had higher CMV infection rate than those who were delivered by caesarean section and/or formula-fed, indicating that saliva samples from the neonates can be contaminated with maternal CMV.…”
Section: Discussionmentioning
confidence: 99%
“…Detection of congenital CMV infection in the neonate needs to be undertaken within three weeks of birth due to the possibility of postnatal infection; for instance, from breast milk [49], and to facilitate prompt interventions [50]. The most suitable diagnostic methodology is real-time polymerase chain reaction using saliva specimens [51][52][53]. Saliva [54] or dried blood spot PCRs [55] have been used in support of newborn hearing loss screening programmes as they offer the capacity to target asymptomatic neonates "at risk" of developing hearing loss and who may benefit from antiviral treatment or other intervention measures [56][57][58].…”
Section: Congenital Cytomegalovirus Infection and Hearing Lossmentioning
confidence: 99%